Risks go beyond the violence: Association between intimate partner violence, mental illness, and substance abuse among females admitted to a rural Level I trauma center. Issue 5 (November 2015) - Hink, Ashley B.; Toschlog, Eric; Waibel, Brett; Bard, Michael
Abstract : BACKGROUND: Intimate partner violence (IPV) is a significant cause of intentional injury among women but remains underrecognized, and its relationship to other risk factors for all-cause injury remains poorly defined. This study aimed to assess IPV and its association with alcohol abuse, illicit substance use, selected mental illnesses, and other risk factors for injury. METHODS: This is a cross-sectional study of prospectively collected data among adult females admitted to a rural, Level I trauma center. Well-validated instruments assessed IPV, substance abuse, and mental illness. Bivariate relationships were assessed with χ 2, odds ratios, and t test analyses. RESULTS: Eighty-one women were enrolled; 51% reported lifetime IPV, and 31% reported past-year IPV. Both groups were significantly more likely to have a mental illness than those without a history of IPV. Those reporting lifetime IPV exposure were significantly more likely to report illicit substance use, and past-year IPV was associated with alcohol abuse (28% vs. 7.1%, p = 0.01). Participants reporting past-year IPV were significantly more likely to have a partner possessing a firearm (40% vs. 12.5%, p = 0.005). CONCLUSION: The experience of lifetime and past-year IPV among women at a Level I, rural trauma center was high, and it was significantly associated with mental illness, substance abuse, and high-risk scenarios for intentional injury including firearm ownership by a significant other. These findings inform the potential value of IPV screening and intervention and suggest that IPV, mental illness, and substance abuse should be considered associated entities in prevention and recidivism reduction efforts in the female trauma population. LEVEL OF EVIDENCE: Prognostic study, level II; therapeutic study, level III.